(untitled) (MAUSAM, 1983)
An Advanced Very High Resolution Radiometer (AVHRR) sensor has been provided in the TIROS-N series of polar orbiting satellites. With this, very high resolution pictures (1.1 km at the sub-satellite point) can be obtained of the earth’s cloud cover. A suitable ground equipment to receive these signals has been set up in the Meteorological Department at New Delhi in February 1981. An attempt has been made m this paper to study the finer aspects of a cyclonic storm which developed in the Bay of Bengal in September 1981. This study reveals the great utility of enhanced satellite pictures in correctly estimating the centre and intensity of weather systems. The formation of an area of intense Cb clouds to the northeast of the system suggests that the system will subsequently move in a northeasterly direction.